Genomewide Expression Profiling Identifies a Novel miRNA-based Signature for the Detection of Peritoneal Metastasis in Patients With Gastric Cancer. Issue 5 (November 2021) - Shimura, Tadanobu; Toden, Shusuke; Kandimalla, Raju; Toiyama, Yuji; Okugawa, Yoshinaga; Kanda, Mitsuro; Baba, Hideo; Kodera, Yasuhiro; Kusunoki, Masato; Goel, Ajay
Abstract : Objective: This study aimed to conduct a genomewide transcriptomic profiling to develop a microRNA (miRNA)-based signature for the identification of peritoneal metastasis (PM) in patients with gastric cancer (GC). Summary Background Data: Even though PM in patients with GC has long been recognized to associate with poor prognosis, currently there is lack of availability of molecular biomarkers for its robust diagnosis. Methods: We performed a systematic biomarker discovery by analyzing miRNA expression profiles in primary tumors from GC patients with and without PM, and subsequently validated the expression of candidate miRNA biomarkers in 3 independent clinical cohorts of 354 patients with advanced GC. Results: Five miRNAs (miR-30a-5p, -134-5p, -337-3p, -659-3p, and -3917) were identified during the initial discovery phase; three of which (miR-30a-5p, -659-3p, and -3917) were significantly overexpressed in the primary tumors from PM-positive patients in the testing cohort ( P = 0.002, 0.04, and 0.007, respectively), and distinguished patients with versus without peritoneal metastasis with the value of area under the curve (AUC) of 0.82. Furthermore, high expression of these miRNAs also associated with poor prognosis (hazard ratio = 2.18, P = 0.04). The efficacy of the combination miRNA signature was subsequently validated in an independent validation cohort (AUC = 0.74). Finally, our miRNA signature when combined together with the macroscopic Borrmann's type score offered a much superior diagnostic in all 3 cohorts (AUC = 0.87, 0.76, and 0.79, respectively). Conclusions: We have established an miRNA-based signature that have a potential to identify peritoneal metastasis in GC patients. Abstract : Supplemental Digital Content is available in the text